2020
DOI: 10.1007/s00415-020-10160-7
|View full text |Cite
|
Sign up to set email alerts
|

The emotional impact of the COVID-19 pandemic on individuals with progressive multiple sclerosis

Abstract: Objective Individuals with pre-existing chronic illness have shown increased anxiety and depression due to COVID-19. Here, we examine the impact of the COVID-19 pandemic on emotional symptomatology and quality of life in individuals with Progressive Multiple Sclerosis (PMS). Methods Data were obtained during a randomized clinical trial on rehabilitation taking place at 11 centers in North America and Europe. Participants included 131 individuals with PMS. Study procedures were interrupted in accordance with go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
82
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(90 citation statements)
references
References 39 publications
3
82
1
4
Order By: Relevance
“…However, a survey carried out among participants of a randomized clinical trial on rehabilitation in progressive MS patients did not confirm significant changes in neuropsychological assessments during the pandemic. ( Chiaravalloti et al, 2020 ) A multi-center study from North America and Europe demonstrated that despite most participants reporting some impact of the virus on their psychological well-being during the pandemic, little changed regarding symptoms of depression and anxiety, and overall quality of life on standardized measures remained mostly unchanged. ( Stojanov et al, 2020 ) Another study from Italy showed that the Beck Depression Inventory and State-Trait Anxiety Inventory scores did not change during pandemic among MS patients.…”
Section: Resultsmentioning
confidence: 99%
“…However, a survey carried out among participants of a randomized clinical trial on rehabilitation in progressive MS patients did not confirm significant changes in neuropsychological assessments during the pandemic. ( Chiaravalloti et al, 2020 ) A multi-center study from North America and Europe demonstrated that despite most participants reporting some impact of the virus on their psychological well-being during the pandemic, little changed regarding symptoms of depression and anxiety, and overall quality of life on standardized measures remained mostly unchanged. ( Stojanov et al, 2020 ) Another study from Italy showed that the Beck Depression Inventory and State-Trait Anxiety Inventory scores did not change during pandemic among MS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies reassessed participants who had participated in trials prior to the pandemic to examine the extent to which distress changed over the studied interval. These studies produced mixed results, suggesting no or modest changes in anxiety or depression (Capuano et al, in press;Stojanov et al, 2020;Chiaravalloti et al, 2020). These studies had the advantage of pre-pandemic data to use as a baseline comparator, but were run on small samples (e.g., N = 67 (Capuano et al, in press)) with restricted characteristics (e.g., only relapsing-remitting MS (Stojanov et al, 2020) or only progressive MS (Chiaravalloti et al, 2020)) due to the inclusion criteria of the trials from which they were drawn.…”
Section: Introductionmentioning
confidence: 99%
“…These studies produced mixed results, suggesting no or modest changes in anxiety or depression (Capuano et al, in press;Stojanov et al, 2020;Chiaravalloti et al, 2020). These studies had the advantage of pre-pandemic data to use as a baseline comparator, but were run on small samples (e.g., N = 67 (Capuano et al, in press)) with restricted characteristics (e.g., only relapsing-remitting MS (Stojanov et al, 2020) or only progressive MS (Chiaravalloti et al, 2020)) due to the inclusion criteria of the trials from which they were drawn. In addition to those distress-focused studies, a large survey study on the healthcare impact of COVID-19 for people living with MS noted that "[p]articipants believed COVID-19 presents a major danger to their health and reported being generally highly worried about the disease" (Vogel et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The psychological impact of COVID-19 in terms of stress, negative emotional reactions (e.g., anxiety, depression), and traumatic responses has been extensively studied in the general population [ 39 ] and to a lower extent also in vulnerable populations, such as chronically ill patients, including patients with MS [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. Moreover, young adults are particularly vulnerable and at greater risk of developing adverse psychological symptoms during the pandemic, as demonstrated in a study by Forte and colleagues [ 40 ] that focused on people under the age of 50.…”
Section: Discussionmentioning
confidence: 99%